PENGARUH TANGIBLE TERHADAP LOYALITAS PELANGGAN DI AULINA LAUNDRY BATAM - Wan Abdurrahman; Andri Wibowo (Puslitabmas Batam Tourism Polytecnic, 2023)
This research aims to determine the effect of tangible on customer loyalty at Aulina laundry Batam. The research method used is a quantitative research method. The data collection technique used is a survey technique with research instruments in the form of a questionnaire. The sample used was based on the slovin formula from a population of 297 and a sample of 84 customers from the entire population who were considered to represent the research data. Data analysis used quantitative descriptive analysis and simple linear analysis. The results of the research show that all statement items are valid and reliable. Hypothesis testing shows the significance value of the coefficients table, obtained T count 0.000 > 0.05 also the distribution list and a real level of 5% obtained Tcount 6.694 > T table 1.989 stating Ha is accepted Ho is rejected. The R2 test shows that the tangible variable has an effect of 0.604 or 60.4% on customer loyalty, the remaining 39.6% is influenced by other variables. So it can be concluded that the tangible variable (X) has a significant effect on customer loyalty (Y).